PENYULUHAN HUKUM PENYELESAIAN SENGKETA KEPEMILIKAN HAK ATAS TANAH DI DESA ONEMBUTE - Hasima, Rahman; Herman, Herman; Heryanti, Heryanti; Yuningsih, Deity; Sulihin, La Ode M.; Yusuf, Haris; Suciati, St. Muslimah (Universitas Halu Oleo, 2024)
The purpose of this community service activity is to improve the community's legal understanding of the procedures for resolving disputes over land ownership both litigation and nonlitigation in Onembute Village, Besulutu District, Konawe Regency so as to provide legal certainty and legal protection of land ownership for the community. The methods used during the process of community service activities include (a) lecture method to provide direct explanation to the community (b) question and answer method to explore community knowledge of the material provided. Legal counseling in the form of lectures is organized to provide an explanation of legal material related to the settlement of land rights ownership disputes. The stages of the activity were carried out as follows: First, the preparation stage, which included location surveys, determination of locations and targets, coordination with the Head of Onembute Village, identification of problems or legal issues of concern to the community, and preparation of materials related to the settlement of land ownership disputes. Second, the Implementation Stage, namely conducting legal counseling by providing material explanations that focus on providing explanations regarding the procedures for resolving disputes over land ownership both litigation and non-litigation as a form of education to the Onembute Village community. The results achieved in this service activity are the community's understanding of the settlement of land ownership disputes before and after the implementation of legal counseling activities shows an increase in community knowledge and understanding of 80%, meaning that the service activities carried out have an impact on increasing the legal knowledge and understanding of the Onembute Village community in resolving land ownership disputes.